The Altitude Project: An international collaborative research project on altitude training in elite swimmers - Rodriguez, F. A.; Levine, B. D. (Sport Science Research Group, INEFC-Barcelona, 2010)
- An Olympic swimmer should improve his/her performance by about 1% within the year leading up to the Olympics to stay in contention for a medal - A recent meta-analysis concluded that the expectable performance benefit from AT/hypoxic training for elite athletes could be as high as 1.6% - In spite of the research carried out over the last four decades, the effectiveness and physiological mechanisms through which AT should enhance sea level performance are still controversial The questions we need to answer are: - Does AT works for elite swimmers? Effectiveness - Why? Mechanisms - How? Methods and strategies When? - Planning and competition after AT For whom? Inter- / intrasubject variability